Bridging the Funding Gap on the Statutory Functions of Statutory Bodies: a Case of Upper Manyame Sub Catchment Council [2013-2015] - Ndowa, Emmanuel C (Midlands State University, 2017)
This study was carried out to bridge the funding gap at Upper Manyame Sub Catchment Council. The research will enhance funding in statutory bodies by searching for other means of funding statutory functions in statutory bodies not relying on the traditional sources of revenue. The researcher used qualitative research approach to analyse the possible ways of bridging the funding gap on the statutory functions of statutory bodies. Qualitative research focuses on phenomena that occur in natural settings that is in real world and they involve studying those phenomena in their complexity. The researcher used the descriptive research design as it portrays an accurate profile of the persons, events and or situations. A sample size of 56 which represented 70% of the population was used by the researcher. The strata comprised Upper Manyame Sub-Catchment Council Staff and stakeholders from the micro-catchments that included institutions in the water sector within Upper Manyame sphere of influence. Simple stratified sampling technique was used to come up with a sample. Questionnaire and interview guide were used in conducting the research. The research found constrained fiscal space and corruption as the causes of funding gap. Strategic Business Units (SBUs) and Public Private Partnerships provide a means of bridging the funding gap. Introducing better revenue collection methods, viable pricing structure, improved budget execution, external funding and retrenchment are some of the methods employed by other countries to curb the funding gap in statutory bodies. The research recommends the setting up of Strategic Business Units and Public Private Partnerships as this improves revenue flows and efficiency in statutory bodies. The originality of the research emanates from the fact that the researcher is the first person to research on Upper Manyame Subcatchment Council for period 2013 to 2015 on the subject of bridging the funding gap in statutory bodies.